2014
DOI: 10.1111/1751-2980.12182
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic colitis: A forgotten entity. Results of a retrospective study in 118 patients

Abstract: IC is majorly occurred in elderly with a female predominance. Cardiovascular disease and its associated risk factors are the most common comorbidities. Left colon is the most affected location of the disease and the overall mortality rate was 4.2%. Physicians should make every effort to identify these patients, especially those with high risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 43 publications
(270 reference statements)
2
23
0
Order By: Relevance
“…The left colon was the most commonly affected segment, while the rectum and ascending colon were the least affected segments. These findings represent general characteristics of IC and are in agreement with previously reported data [1, 2, 57]. However, we found that patients with predisposing factors did not exhibit these characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The left colon was the most commonly affected segment, while the rectum and ascending colon were the least affected segments. These findings represent general characteristics of IC and are in agreement with previously reported data [1, 2, 57]. However, we found that patients with predisposing factors did not exhibit these characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…Many previous studies have referred to predisposing and/or risk factors of IC using terms such as predisposing factor/condition, risk factor, medical condition, comorbidity, underlying medical illness, or etiological factor [5, 8–11, 13, 14]. However, based on our definition, most of the conditions considered in previous studies would be classified as risk factors, not predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Ischaemic colitis (IC), first described by Boley et al [1] and defined as inadequate perfusion caused by impaired colonic blood supply leading to colonic inflammation, is one of the most common gastrointestinal vascular diseases. It frequently occurs in the elderly with a female predominance [2][3][4][5][6], but younger patients may also be affected [7][8][9]. Although underestimated because many cases are transient and misdiagnosed, the incidence of IC in the general population ranges from 4.5 to 44 cases per 100 000 persons per year [10].…”
Section: Introductionmentioning
confidence: 99%
“…The main predisposing factors for IBS are vascular factors and bowel factors. Hypoperfusion, vascular surgery requiring aortic clamping, vasospasm, vasoconstrictor drugs and thromboembolism from hypercoagulable states or cardiac emboli may lead to IBS 30. O'Farrell et al assessed the risk of thromboembolic disease in patients with PC undergoing ADT.…”
Section: Discussionmentioning
confidence: 99%